Patenting whilst being ethical - Abdul Ghani Azmi, Ida Madieha (Sweet & Maxwell Asia, 2009)
The changing landscape of biotechnology research into life sciences and higher life forms warrants that patents for inventions in bio-science would be subjected to many ethical concerns. In Malaysia, the inclusion of "public order" and "morality" into s 31(1) of the Patents Act 1983 as grounds for the refusal of patents raise the issue as to what extent must patent law responses to new technology be informed by moral considerations? In turn, must moral considerations be informed by religious tenets and beliefs? Oliver Mills in his book, Biotechnological Inventions: oral Restraints and Patent Law, contends that patent law is not appropriate, or indeed, designed to regulate biotechnology and any attempt to do so, in particular, by denying patents on the basis of morality, is misplaced. He adds that traditionally patent legislation essentially regulates economic and competition issues and not wider considerations outside the commercial area. Despite his assertion, moral issues have engulfed many patent examiners, offices and courts as many national, international and regional patent laws accept morality as a bar for patentability. In fact, morality has even divided the European countries on nascent biotechnology applications such as stem cells. This article examines the existing cases in the UK and the European Patent Office (EPO) where the issue of morality has been raised. The scope of morality as a ground for the denial of patentability under the TRIPs Agreement2 and the European Patent Convention is also examined. The paper hopes to espouse some guidelines on how to deal with moral issues at the patent office.